2017
DOI: 10.4142/jvs.2017.18.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kinematic gait analysis in young and old Beagle dogs

Abstract: Age-related involution in dogs involves loss of muscle mass and changes in connective tissue and articular cartilage. The aim of this study was to examine whether an age-related influence on joint mobility can be detected in the absence of disease. Five young (mean age 2.0 years) and five old (mean age 10.4 years) healthy and sound Beagle dogs underwent computer-assisted gait analysis during locomotion on a treadmill. Shoulder, elbow, carpal, hip, stifle, and tarsal joint angles including joint angle progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 40 publications
(61 reference statements)
0
29
0
Order By: Relevance
“…First, the three-dimensional motion analysis system using markers attached to the skin might to contain noises of skin movement [ 6 , 22 , 47 ]. Fluoroscopic analysis should be performed to obtain more strict information [ 22 , 40 ]. Second, sEMG is a non-invasive method of attaching electrodes on the surface of the body to reduce the stress of recording, but there is a possibility of “crosstalk” among the target muscle and other nearby muscles [ 6 , 8 , 12 , 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the three-dimensional motion analysis system using markers attached to the skin might to contain noises of skin movement [ 6 , 22 , 47 ]. Fluoroscopic analysis should be performed to obtain more strict information [ 22 , 40 ]. Second, sEMG is a non-invasive method of attaching electrodes on the surface of the body to reduce the stress of recording, but there is a possibility of “crosstalk” among the target muscle and other nearby muscles [ 6 , 8 , 12 , 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researches of the pelvic limb kinematic activity in cats and dogs (Brown et al, 2018) claim that there is a difference in the dynamics, range, nature of movement and pressure load, which is carried out on different parts of the limb (Lorke et al, 2017). The results of our studies confirm that the tarsal joint, as a part of the pelvic limb, undergoes different pressure on different anatomical surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These animals' movement nature presents significant differences. Studies in the field of biomechanics of cat (Brown, Bertocci, Cheffer, & Howland, 2018) and dog (Lorke et al., 2017) movement prove that these animals have a different nature of movement and the load on the joint components is distributed in a different way as well. We observe on daily basis how cats masterfully move on unstable surfaces, which is quite problematic for dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the bull, the joint capsule's synovial mem- With age, the structural components of the joints wear out and the nature of the limbs' movement changes [11]. shown that there are other types of motion in the joint as well.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, high-yield cattle [2,18] often have arthrosis or arthritis of different aetiologies [21]; in the case of a canine [11], especially large breeds [6], mechanical joint injuries often occur, ankylosis or arthrosis develops [1,7]. Such feline breed as Scottish fold have a genetic predisposition for the occurrence of osteochondrodisplasticity of the tarsus and metatarsus [3,10].…”
mentioning
confidence: 99%